2018
DOI: 10.1097/hjh.0000000000001670
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure variability increases with advancing chronic kidney disease stage

Abstract: An increase in short-term SBP-variability was present with advancing CKD stages in a large cohort. This increased SBP-variability may be involved in the sharp elevation of cardiovascular risk with worsening renal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 45 publications
0
47
0
4
Order By: Relevance
“…The pathophysiological meaning of these differences is unclear, but it should be emphasized that BPV (in particular systolic BPV) correlates with arterial stiffness, which in turn is related to aging and increasing SBP (but not DBP) levels. In fact, a recent large study on the relationship between BPV and chronic kidney disease (where arterial stiffness is also relevant) showed that with worsening renal function, an increase occurs in systolic, but not in diastolic, BPV . This might imply that systolic BPV reflects primarily vascular stiffness and aging, while diastolic BPV has a different pathophysiological background such as, for instance, impaired autonomic function with increased sympathetic activity, and endothelial dysfunction …”
Section: Clinical Relevancementioning
confidence: 99%
See 1 more Smart Citation
“…The pathophysiological meaning of these differences is unclear, but it should be emphasized that BPV (in particular systolic BPV) correlates with arterial stiffness, which in turn is related to aging and increasing SBP (but not DBP) levels. In fact, a recent large study on the relationship between BPV and chronic kidney disease (where arterial stiffness is also relevant) showed that with worsening renal function, an increase occurs in systolic, but not in diastolic, BPV . This might imply that systolic BPV reflects primarily vascular stiffness and aging, while diastolic BPV has a different pathophysiological background such as, for instance, impaired autonomic function with increased sympathetic activity, and endothelial dysfunction …”
Section: Clinical Relevancementioning
confidence: 99%
“…Kaplan-Meier curves are shown for subjects with values above (black lines) and below (gray lines) the population median. From Mancia et al 7 used by permission in diastolic, BPV 12. This might imply that systolic BPV reflects primarily vascular stiffness and aging, while diastolic BPV has a different pathophysiological background such as, for instance, impaired autonomic function with increased sympathetic activity, and endothelial dysfunction 13.…”
mentioning
confidence: 99%
“…According to time interval, this metric is divided into long‐term BPV (eg, visit‐by‐visit BPV), mid‐term BPV (eg, day‐by‐day BPV within days or weeks), and short‐term BPV (eg, beat‐to‐beat and hour‐to‐hour BPV) . CKD is associated with increased BPV, and this association gets stronger with CKD stages advancing . As BPV has been shown to be a risk factor for cardiovascular events and all‐cause mortality, it may be related with the high mortality risk of CKD patients with VC.…”
Section: Introductionmentioning
confidence: 99%
“…10 CKD is associated with increased BPV, and this association gets stronger with CKD stages advancing. 11 As BPV has been shown to be a risk factor for cardiovascular events and all-cause mortality, [12][13][14][15] it may be related with the high mortality risk of CKD patients with VC.…”
Section: Introductionmentioning
confidence: 99%
“…BP variability (BPV) is also increased in patients with DM and is mainly associated with deranged autonomic control of circulation and increased arterial stiffness [8]. Similarly, results from a large cohort study from the Spanish ambulatory blood pressure monitoring (ABPM) registry suggested that shortterm BPV was higher in patients with compared to those without CKD and all indexes of systolic BPV were gradually increasing with advancing CKD stages [9].…”
Section: Introductionmentioning
confidence: 99%